Implementation of the STAD Model with Smart Envelope Quiz Media on Number Patterns in Improving Student's Critical Thinking on Number Pattern Material - Panglipur, Indah Rahayu; Ayu, Yesi Nindi; Anas, Aswar (Journal of English Language and Education, 2025)
This study aims to determine the implementation of the STAD Model with the Smart Envelope Quiz Media Number Pattern in improving students' critical thinking on number pattern material. In this study, the tools and materials used were origami paper, scissors, glue, and buffalo paper. Learning media has a very important role. With learning media, teachers can use it as a tool to provide learning materials so that learning in the classroom becomes active, interesting and fun. The learning model used is the STAD Model, a learning model that emphasizes students to work together in groups. The researcher used a qualitative method with a descriptive approach. Data collection obtained in this study were interviews, observations, and documentation. This research was conducted at SMA Plus Bustanul Ulum Puger, Mlokorejo Jember. The location of the research is Jl. Kh Abdullah yaqien no. 1-5 puger, jember. the subjects of this study were female students of class 11 SMA Plus Bustanul Ulum Mlokorejo, Jember with a sample of 1 student Nur Fitria (S1).